DIFFERENCE IN LEARNING SATISFACTION OF STUDENTS OF THE UNIVERSITY OF FLORES PHYSICS EDUCATION STUDY PROGRAM BEFORE AND DURING THE COVID-19 PANDEMIC - Silvia Triana Juita; Ilyas Ilyas; Yasinta Embu Ika (Pendidikan Fisika UIN Alauddin Makassar, 2021)
This study aims to find out the difference in student learning satisfaction of the University of Flores Physics Education Study Program before and during the Covid-19 pandemic. The research methods used are quantitative methods with the type of research, namely survey research, as well as data collection techniques using questionnaires. The sample taken in this study was a student of Physics Education University of Flores semester IV, VI and VIII which amounted to 65 people. The data analysis technique used in this study consists of several parts, namely: descriptive analysis, normality test, paired sample t-test and hypothesis test that will be analyzed with the help of SPSS Statistics 24 software. The results of the data analysis concluded that there were differences in student satisfaction of the University of Flores Physics Education Study Program before and during the covid-19 pandemic. This is seen from Sig. (2-tailed) < 0.05, which is 0.001 < 0.05 then the data showed a significant difference.